Functional Biopolymers (Springer Series on Polymer and Composite Materials,, 2018)
This book presents the synthesis, processing and application of selected functional biopolymers as new advanced materials. It reviews theoretical advances as well as experimental results, opening new avenues for researchers in the field of polymers and sustainable materials. The book covers various aspects, including the structural analysis of functional biopolymers based materials; functional biopolymer blends; films, fibers, foams, composites and different advanced applications. A special emphasis is on cellulose-based functional polymers, but other types of functional biopolymers (e.g. from chitosan, starch, or plant oils) are also described.